DEVELOPMENT OF INDIVIDUAL STYLE OF ACTIVITY [FUTURE TEACHER AS A PROBLEM OF QUALITY MANAGEMENT HIS PREPARATIONS (Pedagogy of Higher and Secondary Education, 2008)
In article problems of development of individual style of activity of the future teachers as quality managements of formation (education) are considered.